Electrochemically Induced Formation of Cytochrome c Oligomers at Soft Interfaces - Alvarez de Eulate, Eva; O'Sullivan, S.; Arrigan, Damien (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
The formation of cytochrome c oligomers was induced at liquid−gel and liquid−liquid interfaces via electroadsorption. At an optimum interfacial potential (Eads=0.975 V), the protein was accumulated at these soft interfaces. It was found that as the concentration of adsorbed protein increased, a single voltammetric peak evolved into double and triple peaks (tads=300 s). Analysis of the protein that accumulated at the interfaces by polyacrylamide gel electrophoresis indicated the presence of oligomeric species, corresponding to dimers (ca. 27 kD), trimers (ca. 35 kD), and even larger species (>250 kD) after prolonged electroadsorption (tads=2 h) at macro-scale soft interfaces. Accordingly, it was possible to electrochemically induce oligomerisation at these soft interfaces, which can be tuned through experimental factors such as interfacial potential difference, electroadsorption time, and bulk solution concentration. These results suggest the use of electrochemistry at soft interfaces as a strategy for the investigation of protein oligomerisation and its inhibition.